Surface Listening: Free Association and Recitation in the Wooster Group's The B-Side: "Negro Folklore from Texas State Prisons" A Record Album Interpretation - Napolin, Julie Beth (Performance Matters, 2022)
This essay is a critical narrative of an experience of listening to the Wooster Group’s The B-Side: “Negro Folklore from Texas State Prisons” A Record Album Interpretation (2017). The performance is a verbatim recitation of a 1965 ethnographic recording by Bruce Jackson of African American men toasting and singing works songs just before Texas prisons were desegregated. African American actors on stage hear the album through earpieces and re-perform songs and toasts in real time as the LP plays on a turntable visible (but mostly inaudible) to the audience. Their interpretation “transmits” the album to an audience. The essay, continuing that work of transduction, draws from the psychoanalytic notion of “free association” in order to think through the possibilities and limitations of listening across race and gender. It argues that association is a reciprocal way of listening and making theatre. It is also a way of working through history (recorded and unrecorded) in the face of intractable frameworks of racial antagonism in the United States. The essay assembles and “associates” photographs, songs, and excerpts of interviews with the show’s makers, as well as pairing concepts from the literature of listening and the archive of Black sonic performance.